CIPP Evaluation Study on Listening for Daily Context Course in English Language Education Study Program - Murtini, Ni Made Wersi; Ni Nyoman Padmadewi; I.G.A. Lokita Purnamika Utami (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
The Listening for Daily Context course in the English Language Education Study Program, Mahasaraswati University, Denpasar, has never been evaluated even though listening is an important skill in language learning. This study aims to evaluate the implementation of the course using the CIPP (Context, Input, Process, Product) evaluation model. This research is a qualitative study involving study program managers, lecturers, and students as participants. Data collection was carried out through open interviews and document studies. The results of the study show that this course is well designed, in accordance with clear curriculum goals, combines theory and practice, and is supported by adequate human resources and facilities. The evaluation also showed that this course was proactive in overcoming challenges, integrating feedback from students, and having a positive impact on students' listening comprehension and communication skills. However, there is still a need for improvements in technological updates and the use of more authentic materials. This study concludes that this course is effective in developing students' listening skills and recommends increased use of technology as well as opportunities for listening practice in real contexts to prepare students to communicate academically and professionally. This evaluation provides insight to continue to improve this program so that students are ready to communicate in English academically and professionally.